Radiotherapy and chemoradiotherapy for postoperative recurrence in patients with esophageal squamous cell carcinoma - Qing Liu; Xue‐Hua Tu; Rui‐Xuan Yu; Hong‐Ying Wen; Xiao‐Guang Guo; Dai‐Yuan Ma; Kai‐Yuan Jiang; Dong Tian (Cancer Medicine)
Abstract Background The optimal treatment for esophageal squamous cell carcinoma (ESCC) patients with postoperative recurrence remains controversial. We aimed to evaluate the effects of radiotherapy (RT) and chemoradiotherapy (CRT) on postoperative recurrence in ESCC patients. Methods Recurrence ESCC patients who received salvage RT and CRT from January 2015 to January 2019 were retrospectively reviewed. Post‐recurrence survival (PRS) and prognostic factors were evaluated by Kaplan–Meier and Cox proportional hazards models, respectively. Subgroup analyses were performed based on pathological lymph node (LN) status (negative/positive) to evaluate the differences in salvage treatments and toxic reaction. Results A total of 170 patients were enrolled, with a median age of 60 years (range 43–77). No significant difference was found in the median PRS between the salvage RT and CRT groups (p > 0.05). Multivariate analysis revealed that TNM stage III and IV, macroscopic medullary type, and distant metastasis recurrence pattern were independent prognostic factors (all p < 0.05) for PRS. Salvage treatment was not associated with PRS (p = 0.897). However, in patients with negative LN, CRT was associated with prolonged survival (p = 0.043) and had no significant differences in toxic reactions compared to RT (p = 0.924). In addition, RT showed better prognoses (p = 0.020) and lower toxic reactions (p = 0.030) than CRT in patients with positive LNs. Conclusions Based on prognosis and toxic reactions, ESCC recurrence patients with negative LNs could benefit from CRT, but RT should be recommended for patients with positive LNs.